Peran Kepemimpinan Etis dalam Memoderasi Hubungan Good Corporate Governance dan Internal Control terhadap Pencegahan Fraud Accounting - Danduru, Beatrix Putri; Beloan, Bertha; M, Theresia Endang; Valensia, Egi (Juara: Jurnal Riset Akuntansi, 2025)
This research aims to analyze the influence of good corporate governance (GCG) and internal control on accounting fraud prevention and to examine the role of ethical leadership as a moderating variable. The study employed a quantitative approach using the Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis method. Data were collected by distributing questionnaires to managers, finance and accounting staff, operational staff, and officials at State-Owned Enterprises (BUMN) located in Makassar City. The results indicate that good corporate governance and internal control have a positive and significant effect on accounting fraud prevention. The role of ethical leadership was proven to moderate the relationship between good corporate governance and accounting fraud prevention, but it does not moderate the relationship between internal control and accounting fraud prevention. These findings suggest that the role of ethical leadership is crucial in strengthening the cultural and corporate governance mechanisms (soft mechanism), but its role is not dominant in supporting formal structural mechanisms (hard mechanism) such as internal control.